Factors that assist co-operative enterprises to be successful in South Africa - Mokhele, Mohau Martin (My University, 2014)
Context The South African government is looking at co-operatives as one way of addressing poverty and high unemployment rates in the country. However, their impact on addressing these challenges is somewhat minimal due to their high rate of failure. The objective of this study is to research factors that enable these organisations to be successful as business enterprises. A brief statement of the problem The problem is that co-operatives experience a high failure rate in South Africa. It is currently estimated by the Department of Trade and Industry to be at 88%. These organisations are important due to their ability to create employment, reduce poverty and improve the economic participation of the marginalised communities. The study looked at the factors that contribute to the success of co-operative enterprises in South Africa. The method of data collection The research was done through in-depth interviews with respondents from cooperative companies and stakeholders in Gauteng and the Free-state. A questionnaire was prepared to collect specific information about these organisations through an interview process in order to understand and answer the research problem. Two different types of questionnaires were prepared for co-operative organisations and stakeholder organisations. Audio recordings of the interviews were kept as a reference to the actual discussions and meetings. iii Key findings The available literature indicate that co-operatives fail due to a number of challenges in South Africa; which are lack of appropriate skills, resources and understanding of the co-operative organisations and the availability of markets for their products. These are the main constraints to their success and sustainability. The research study found various factors that can improve the performance and success of these organisations which included; the right kind of support from government and other stakeholders that is channelled towards training and capacity building within cooperatives. This training would create an enabling environment for these organisations to operate in and improve their productivity. The provision of finance to fund viable start-up ventures and expansion plans would also contribute to making them successful. Key message The importance of co-operatives in South Africa was confirmed due to their ability to balance economic and social benefits. However, the success and benefits, where they exist, of these organisations need to be well communicated and documented to improve their attractiveness and encourage other entrepreneurs to follow the collective action route in forming businesses. The understanding of co-operatives and appreciation of the seven principles that characterise them is of utmost importance to their sustainability and success as they describe the fundamental principles that these organisations universally operate under and contribute to society. The stakeholders including; government through the DTI, provincial department and development finance institutions need to support and continue to promote these collective organisations to ensure and project their success as drivers of economic development in communities and rural areas.
Keywords: Cooperative societies , Producer cooperatives , Business enterprises -- South Africa.